Improving The Effectiveness of Commercial Bank Employess in Cross River State Through Appropriate Remuneration - Angioha, Pius U.; Agba, Rose U.; Kenneth, Beauty U.; Ishie, Eno U. (Quantitative Economics and Management Studies, 2021)
The study specifically examines the correlation between remuneration and the effectiveness of employees in commercial banks in cross river state, adopting a survey method, data was collected from 232 participants employed by five commercial banks in cross river state. The participants were selected using the proportional stratified and simple random sampling technique. A self-developed questionnaire was adopted to elicit the required information for the study. Data collected was analyzed using descriptive and inferential statistics. out of the 232 distributed questionnaires, 213 was returned and used for analysis. Result revealed a correlation between remuneration and the effectiveness of employees in commercial banks in cross river state. From the analysis 21.8 per cent of the variance in the effectiveness of bank's employees is accounted for by remuneration. The study concludes that bank the management of banks need to take into cognizance the economic situation in the country and improve on the take-home package of their employees.